HUBUNGAN TINGKAT KECEMASAN DENGAN PERILAKU MEROKOK MAHASISWA LAKI-LAKI SELAMA DARING PADA MASA PANDEMI COVID-19 - Mustakim, Mustakim; Kusumastuti, Nurry Ayuningtyas (Nusantara Hasana Berdikari, 2022)
At the beginning of 2020 Covid-19 in Indonesia experienced a significant increase in the increase in the spread of Covid-19 which affected the teaching and learning process of all students, both students and students in Indonesia. The impact of Covid-19 is the implementation of Study from home using an online learning system. The impact on students during the pandemic showed much higher levels of anxiety, depression, and stress compared to students in normal times. One of the negative effects that appears on male students is smoking, which is one of the most frequently used anxiety diversion methods. Objective: to determine the relationship between anxiety levels and smoking behavior of male students while online during the Covid-19 pandemic at the University of Muhammadiyah Tangerang (UMT). This study uses a quantitative method with a cross sectional approach. Data analysis in this study used univariate analysis and bivariate analysis using Spearman's test. There is a relationship between the level of anxiety and smoking behavior, with a p-value of 0.000 <0.05 with a sufficient correlation strength coefficient of 0.468. There is a sufficient relationship between the level of anxiety and smoking behavior of male students while online during the Covid-19 pandemic.